New Insights Into Vertigo Attack Frequency as a Predictor of Ischemic Stroke - Qiu, Dongxu; Zhang, Lei; Deng, Jun; Xia, Zhiwei; Duan, Jingfeng; Wang, Juan; Zhang, Rongsen (Frontiers in Neurology, 2020)
Background: Recurrent attacks of vertigo account for 2.6 million emergency department visits per year in the USA, of which more than 4% are attributable to ischemic infarction. However, few studies have investigated the frequency of attacks of vertigo before an ischemic stroke. Methods: We conducted this retrospective analysis and manually screened the medical records of 231 patients who experienced recurrent attacks of vertigo prior to an ischemic stroke. Patients were divided into four different groups based on the frequency of vertigo attacks as well as the region of ischemic infarction. Those with ≤2 attacks of vertigo preceding the ischemic stroke were defined as the low-frequency group. Those with ≥3 attacks were defined as the high-frequency group. Clinical parameters, including vascular risk factors, average National Institutes of Health Stroke Scale (NIHSS) score, and infarction volume, were compared between the groups. Results: On analysis, we found that patients with posterior infarction in the high-frequency group exhibited a higher prevalence of vertebral artery stenosis. However, the incidence of diabetes mellitus (DM) was higher in the low-frequency group. In addition, patients with posterior infarction in the low-frequency group were more active in seeking medical intervention after an attack of vertigo. Notably, the brain stem, especially the lateral medullary region, had a higher probability of being involved in posterior infarction in the high-frequency group. However, the cerebellum was more commonly involved in posterior infarction in the low-frequency group. Conclusions: Our findings indicate that the clinical parameters, including arterial stenosis, DM, and magnetic resonance imaging (MRI) findings, differed between the low- and high-frequency groups. We also found that patients in the low-frequency group were more willing to seek medical intervention after the attacks of vertigo. These findings could be valuable for clinicians to focus on specific examination of the patients according to the frequency of vertigo attacks.